2009
DOI: 10.1177/155892500900400304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spinning Parameters and Recovered Fibers from Cotton Waste on the Uniformity and Hairiness of Rotor Spun Yarn

Abstract: Improving raw material exploitation has become the most important challenge facing scientific and industrial community. In this paper, we have studied the effect of percentage of fibres recovered from cotton wastes and different spinning parameters on the hairiness, the uniformity and the level of irregularity of the rotor yarn. Results indicate that yarn count, rotor parameters (diameter and form) and rotor speed have an effect as significant as waste proportion. With a good choice of spinning parameters, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…3,4,21,22 The quality of production waste is better in comparison with post-production waste mainly in terms of fiber length and its variability. 1822 Many authors 122 concentrate on the quality of fibrous material components at the beginning of the process by the standard parameters used for definition of cotton fibers. On the other hand, they do not indicate the quality of fibrous materials from the point of view of amount of neps, dust, and impurities amount.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,21,22 The quality of production waste is better in comparison with post-production waste mainly in terms of fiber length and its variability. 1822 Many authors 122 concentrate on the quality of fibrous material components at the beginning of the process by the standard parameters used for definition of cotton fibers. On the other hand, they do not indicate the quality of fibrous materials from the point of view of amount of neps, dust, and impurities amount.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated how to optimally blend and reuse various production cotton waste, mainly carding stipes with addition of noils, and if necessary virgin cotton or polyester to get the high or regular quality of yarns has been demonstrated. 2,[6][7][8][9][10][11] The study on processing of cotton ginning waste into openend rotor yarn is presented in the literature 12,13 as is the processing of fully recycled fibers from fabric scraps. [14][15][16] The verification of suitable setting of the production line and selection of machine parts relevant for processing of cotton waste was also proven.…”
mentioning
confidence: 99%
“…Greek cotton was chosen due to the suitable fiber length for blending with recovered fibers. They have reported that yarn appearance, level of irregularity, and the yarn uniformity did not affect up to 25% waste ratio [17,18].…”
Section: Cotton Wastes In Spinning Millmentioning
confidence: 98%
“…Higher waste fiber amounts can be used for medium and coarser rotor yarns, about 10 and 20%, respectively. Opening and cleaning lines of combed ring spinning [17,18]. According to Klein, waste generation in spinning mills of industrialized countries differs from machine to machine.…”
Section: Cotton Wastes In Spinning Millmentioning
confidence: 99%
“…The quantitative and qualitative assessment of textile fiber waste is often linked with waste management and valorization. HALIMI et al evaluated the waste percentage and the good fiber fraction for two cleaning machines and a card before the weaving step [8][9][10]. After this, the quality of recovered fibers was reviewed and confronted to other virgin material.…”
Section: Introductionmentioning
confidence: 99%